Digital Twin Finite Element Model for Fault Diagnosis of Rotor System - Lee, Dongmin; Park, Cheonha; Kim, Chang Wan; Jung, Joon Ha; Oh, Hyunseok (Transactions of the Korean Society of Mechanical Engineers, A, 2023)
This study describes the development of a digital twin finite element (FE) model for rotor systems. The FE model incorporates the shape of the rotor system, material properties, and boundary conditions when the rotor system operates normally. Disk mass imbalance and angular misalignment are expressed in the form of a force equation. The vibration of the testbed is calculated using the FE model by incorporating the force equation. The FE model is calibrated by adjusting the bearing support stiffness and bending coupling coefficient to minimize the discrepancy between vibration data from the testbed and simulation model. The validity of the model is verified by comparing the vibration data from the newly acquired testbed with those of the calculated FE model. The developed FE model can alleviate the problem of data absence or data imbalance for fault diagnosis of actual rotor system.
Keywords: Faults diagnosis; Finite element analyse; Finite element modelling (FEM); Force equations; Material boundaries; Misalignment; Model calibration; Rotor systems; Unbalance; Vibration data; Digital Twin; Finite Element Analysis; Misalignment; Model Calibration; Unbalance